The Integration of Islam and Science Praxis in Madrasah Ibtidaiyah (MI) - Firdausy, Fa’ila Ulfa Zahrotul; Muharom, Fauzi (The Future of Education Journal, 2025)
The integration of Islamic religion and science in Madrasah Ibtidaiyah (MI) is a strategic step to eliminate the separation between religious education and general knowledge that still occurs today. This research aims to analyze the basic concepts, philosophical foundations, implementation principles, and real practices of integration in MI. Using the literature study method and descriptive-analytical approach, this research found that integration can be done through thematic curriculum development that integrates Qur'anic verses with science lessons, the application of contextual and science-based learning methods, and evaluation that covers the cognitive, affective and spiritual aspects of students. Teachers have a key role as facilitators of Islamic values as well as innovators in developing creative learning media. The research findings show that this integration can present the profile of graduates who are intellectually smart, strong in spiritual aspects, and have a strong Islamic character, making it relevant as a solution in Islamic basic education in modern times.